Seed germination performance in Trigonella foenum-graecum L. under the influence of Gibberellic acid, Oxygenated Peptone and Vermiwash - Jagtap DK; Kashid LM; Jakhi PS (International Journal of Life Sciences, 2015)
Oxygenated peptones and Vermiwash are commonly used in organic farming practices. In the present investigation, experiments were carried out to study the influence of Gibberellic acid (50 ppm), Oxygenated peptone (1% aqueous) and Vermiwash (20%) on fenugreek (Trigonella foenum-graecum L.) var. early bunching during seed germination by using petri-plate method. Distilled water was considered as control. Oxygenated peptone and Vermiwash showed promontory effect on germination percentage. All three treatments stimulated vigour index and also showed enhancement in fresh and dry weights of root and shoot. Oxygenated peptone and Vermiwash showed supremacy in root length while GA treatment remarkably enhanced shoot length. Oxygenated peptone, Vermiwash and GA treatments showed significant improvement in the amount of total carbohydrates, soluble proteins and activities of enzymes like amylase, protease and catalase. The study revealed that Vermiwash, Oxygenated peptone and GA improve the process of germination with positive alteration in biochemical aspects.